Designing social studies instruction grounded in ecopedagogy and engagement theory: Cultivating university students’ critical consciousness of environmental issues - Wardani; Hestiningtyas, Widya; Kesuma, Tubagus Ali Rachman Puja; Kurniawan, Andree Tiono (Jurnal Teori dan Praksis Pembelajaran IPS, 2025)
The research aims to develop a social studies learning model using the ecopedagogy approach and engagement theory to increase students’ critical awareness of environmental issues. Many studies indicate an ongoing environmental crisis in our environment. Universities have a responsibility to foster transformative awareness to act responsibly, beyond cognitive understanding of the environment. The ecopedagogy framework, as an approach to building critical pedagogy, prioritizes sustainability, environmental justice, and optimizes students’ ability to understand the environment. In addition, engagement theory emphasizes meaningful learning through collaboration and the use of technology. This research uses a qualitative method with a Design-Based Research (DBR) approach that has a series of cycles starting from planning, implementation, evaluation, and reflection in social studies learning. Data collection techniques use observation, interviews, and documentation that are analyzed in an integrated manner. The results of the study show that the combination of the ecopedagogy learning model with engagement theory produces a social studies learning model that can significantly increase critical awareness, active participation, and critical thinking in social studies learning, namely the Eco-Engaged Learning Cycle (EELC). The EELC learning model is a real strategy that contributes to addressing environmental issues critically and participatory. Future research is recommended to test and refine this model in diverse educational contexts and across different levels of education, thereby expanding its applicability and impact on environmental education.